2010
DOI: 10.1111/j.1538-7836.2010.03887.x
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale (PFO) and cryptogenic stroke

Abstract: To cite this article: Anzola GP, Giusti del Giardino L, Piras MP. Patent foramen ovale (PFO) and cryptogenic stroke. J Thromb Haemost 2010; 8: 1675-7.Julius Cohnheim, a German pathologist, is credited, in 1877, as the first to hypothesize that the failed closure after birth of the foramen ovale (the interatrial opening that allows the oxygenated blood from the placenta to bypass the non-functioning pulmonary circulation and enter the fetal systemic circulation) might underlie the spreading of venous emboli to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(40 reference statements)
0
3
0
2
Order By: Relevance
“…Patent foramen ovale (PFO) arises when children older than 3 years do not have their foramen ovale closed. Approximately 10%–35% of adults have a PFO in the general population, but the frequency is even higher in cryptogenic stroke (CS) patients (Anzola, Giusti Del Giardino, & Piras, ; Belvis et al, ; Katsanos et al, ; Souteyrand et al, ; Yue, Zhai, & Wei, ). Since the PFO shunt is too small, PFO had long been considered a nonserious clinical presentation (Hara et al, ; Zhao, Cheng, Zhang, Li, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patent foramen ovale (PFO) arises when children older than 3 years do not have their foramen ovale closed. Approximately 10%–35% of adults have a PFO in the general population, but the frequency is even higher in cryptogenic stroke (CS) patients (Anzola, Giusti Del Giardino, & Piras, ; Belvis et al, ; Katsanos et al, ; Souteyrand et al, ; Yue, Zhai, & Wei, ). Since the PFO shunt is too small, PFO had long been considered a nonserious clinical presentation (Hara et al, ; Zhao, Cheng, Zhang, Li, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, however, increasing studies have shown that PFO patients have a higher morbidity of stroke, migraines, and other relevant diseases than normal population. Hence, more attention has been paid in particular to the relationship between PFO and CS (Anzola et al, ; Handke et al, ; Thaler & Wahl, ).…”
Section: Introductionmentioning
confidence: 99%
“…Значимо возрастает клиническая значимость АМПП при ООО, сети Киари, удлиненном ЕК [52,104,105]. Данные о взаимосвязи АМПП и ПМК многочисленны, но неоднозначны [101,106,107,108,109,110,111].…”
Section: клиническая диагностикаunclassified
“…Изолированное ООО встречается реже, чем в сочетании с АМПП [104]. В 70 % случаев ООО сочетается с ЕК [150] и в 83 % -с сетью Киари [120].…”
Section: взаимосвязи структурных аномалий сердца и их клиническое знаunclassified
“…Observational studies have identified several anatomic and clinical factors associated with PFO that may increase the likelihood that PFO is the cause of the primary or recurrent stroke (Fig. —bottom).…”
Section: Evaluation For Cryptogenic Stroke and Pfomentioning
confidence: 99%